Pop Art - Osterwold, Tilman (Köln : Benedikt Taschen Verlag GmbH, 1999)
Everything Is Beautiful, raved Andy Warhol in raptures at the glamour of modern life, consumer society, the world of the media and its stars. And in so saying, he was expressing the feelings of a generation who felt their age was dawning, an age of Love and Freedom. In art, too, a new attitude towards the present was making itself felt. Jasper Johns, Roy Lichtenstein, Claes Oldenburg, Robert Rauschenberg, James Rosenquist, Tom Wesselmann, Richard Hamilton and many other artists were discovering Marilyn Monroe, Elvis Presley, Coca Cola, comics, advertising, household appliances and food cans as an independant aesthetic reality. Popularity and triviality were no longer terms of abuse, but were central to a new understanding of an art whose aim was to break down the barriers between art and life. The author gives us a detailed account of the styles, themes and sources of Pop Art, investigating its development in different countries and providing biographies of its leading exponents.
Arman ; Artschwager, Richard ; Barker, Clive ; Bengston, Billy Al ; Blake, Peter ; Boshier, Derek ; Caulfield, Patrick ; Christo ; D'Arcangelo, Allan ; Dine, Jim ; Errò ; Fahlström, Öyvind ; Goode, Joe ; Grooms, Red ; Hains, Raymond ; Hamilton, Richard ; Hockney, David ; Indiana, Robert ; Johns, Jasper ; Johnson, Ray ; Jones, Allen ; Kanovitz, Howard ; Kienholz, Edward ; Kitaj, R.B. ; Lichtenstein, Roy ; Lindner, Richard ; Marisol ; Oldenburg, Claes ; Paolozzi, Eduardo ; Phillips, Peter ; Ramos, Mel ; Rauschenberg, Robert ; Richter, Gerhard ; Rivers, Larry ; Rosenquist, James ; Ruscha, Edward ; Segal, George ; Smith, Richard ; Thiebaud, Wayne ; Tilson, Joe ; Vostell, Wolf ; Warhol, Andy ; Wesselmann, Tom ; Westermann, Horace Clifford
Engels
boek
Keywords: Europa; Groot-Brittannië; U.S.A.